Organizational Citizenship Behavior in the Public and Private Sectors: A Multilevel Test of Public Service Motivation and Traditional Antecedents. (June 2020) - Ingrams, Alex
Scholarly knowledge of organizational citizenship behavior (OCB) has developed significantly in the private and public sectors. However, comparisons between sectors have not been advanced. This article aims to address the gap with hierarchical linear modeling of OCB antecedents across sectors, accounting for individual- and sector-level differences. The results show a significant association between public service motivation (PSM) and OCB, as well as several other central correlates of OCB in the public sector: goal clarity, job satisfaction, and leader–member exchange (LMX). In addition, although there are marginally higher levels of OCB in the public sector, the interaction effect of sector and PSM is not significant. This finding suggests the effect of PSM on OCB is important across sectors rather than solely being a function of public sector employment.